Improving Civics Education Learning Outcomes in 1908 National Awakening Spirit Materials by Using Problem Solving Learning Methods - Mahmud Zuhdi (CV. Creative Tugu Pena, 2022)
Implementing teaching plays an important role for the success of teaching proces. Good teaching implementation was strongly influenced by good planning as well. In addition, the implementation of teaching can be successful if supported by the existence and enthusiasm of teachers and students. Intensive study conducted by the Directorate of Education (1996-1997) to identify students' learning and understanding in accordance with the curriculum. The aim of this article was to determine the extent to which the application of the Problem Solving learning method was applied in improving the Learning Outcomes of the National Awakening Spirit of National Awakening Material in 1908. The researcher used classroom action research method. This action research was conducted in 3 cycles. The result showed that it be able to improve the Learning Outcomes of the National Awakening Spirit of the Year 1908 by achieving ideal standards. From 64.31% in cycle 1, it can increase in cycle 2 to 74.92% and cycle 3 to 82.15%, and classically it has reached completeness. The results of this action research indicated that the application of the Problem Solving learning method can improve the Learning Outcomes of the 1908 National Awakening Spirit of Class VIII A PPKn with completeness reaching 100%, thus the application of the Problem Solving learning method was effective in improving learning outcomes in PPKn subjects at MTs Aswaja Tengaran. Keywords: Students Learning Outcomes, Problem Solving Learning Method, Improving Civics Education